Effect of Inclusion of Probiotics Consortium in the Diets on Growth, Digestibility of Nutrients and Blood Parameters in Labrador Dogs - Mandhotra, Digvijayaditya Singh; Sethi, A.P.S.; Panwar, Harsh; Sikka, S. S. (Indian Journal of Animal Nutrition, 2017)
An experiment was conducted to evaluate the effect of feeding probiotic consortium on digestibility of the nutrients and blood parameters in dogs. Twelve different bacterial cultures were procured from NCDC, NDRI, Karnal and were used to form two consortia depending upon their compatibility and probiotic characters. Nine Labrador dogs were divided in three groups of 3 animals based on body weight and age. Three diets i.e. basal diet as control (T0), basal diet with probiotic consortium I (T1) and the basal diet swith probiotic consortium II (T2) were prepared. The experimental feeding was carried out for twelve weeks. A digestibility trial was conducted to ascertain the effect on the nutrient digestibility. The body weight gain and feed conversion ratio were similar in all the groups. The plasma total protein concentration was lower in groups T1 and T2 as compared to group T0, however, the values of Hb, glucose, total cholesterol and BUN were similar in all the groups. The addition of probiotic consortium in the diet increased the digestibility of EE, CP, CF, NDF and ADF without affecting blood parameters and growth in Labarador dogs.